Understanding the mutualistic interaction between greater honeyguides and four co-existing human cultures in northern Tanzania - Laltaika, Eliupendo Alaitetei (Department of Biological Sciences, 2022)
Greater honeyguides (Indicator indicator) eat wax, and to obtain it, they guide people to bees' nests by flying from one tree to another while giving a distinctive chattering call, in the direction of a wild bees' nest. This relationship is mutually beneficial: the hunters harvest valuable honey, and the honeyguides feed on the beeswax leftover from the harvest. In northern Tanzania, multiple human cultural groups live in close proximity in the same geographical area, and most of them practice honey-hunting with the help of honeyguides. Yet, they may differ in cultural traits that determine their relationship with honeyguides. To map this, I visited 12 villages to interview 129 people from the Hadzabe, Ndorobo, Maasai, Sonjo and Datoga cultural groups about their honey-hunting activities and interactions with honeyguides. Specifically, this thesis investigates (i) how important honey and honeyguides are to each human cultural group; (ii) the sounds used by each group to communicate with honeyguides, to test whether honeyguides may have to learn multiple human ‘languages' in the same geographical area; (iii) the traditions of each cultural group concerning whether and how to reward the honeyguide after it has shown them a bees' nest; (iv) the methods used by different cultures to subdue the bees, and whether some of these are more sustainable than the use of fire; (v) each cultural group's ownership traditions concerning wild bees' nests, which might incentivise sustainable honey-hunting practices; and finally, (iv) the likely impact of cultural change for the future of the honeyguide-human mutualism. Overall, my results suggest that (i) the human-honeyguide mutualism still thrives in this region, particularly in the Hadzabe and Ndorobo cultural groups who do not practice bee-keeping; (ii) people from each culture are largely consistent in the calls they use to communicate with honeyguides, but that these calls differ between cultures (but are most similar between the Maasai and Ndorobo people who are culturally close despite many differences in lifestyle); (iii) many cultures deliberately ‘keep the honeyguide hungry' so it shows them more bees' nests, by either concealing the wax (particularly Hadzabe people) or by pretending not to see the bees' nest the bird shows them (particularly Ndorobo people); (iv) people commonly use methods besides fire to subdue bees, specifically because these methods are less harmful to bees, and particularly a fungus called ‘Engishimui' (Scleroderma verrucosum); (v) only the Ndorobo currently have ownership traditions associated with wild bees' nests; and (vi) cultural changes such as bee-keeping were sometimes reported to underlie declines in humanhoney-guide mutualism, but that environmental deterioration of bee habitat because of climate change and pastoralist activities seem to be the biggest threats to the still very active Hadzabe and Ndorobo honey-hunting cultures.